APLIKASI KOMPOS TANDAN KOSONG KELAPA SAWIT DAN DOLOMIT PADA MEDIUM SUB SOIL INCEPTISOL UNTUK PEMBIBITAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Purba, Mazmur Rahmat Amindo; Amri, Al Ikhsan; ', Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is determining the effect of someÂ  treatment combinations and to determine the combination of best compost bunches empty palm oil and dolomite that could support growth seeds palm oil plantations in a main nursery. This research has been conducted in the experimental field, Agriculture Faculty, University of Riau from April to July 2015. The research used Completely Randomized Design Factorial that consisting of two factors. The first factor is giving compost bunches empty palm oil which consist of three levels, they are: K1= 37,5 g/polybag, K2= 75 g/polybag and K3= 112,5 g/polybag. The second factor is giving lime dolomite (CaMg (CO3)2) which consist of three levels, they are: D1=9 g/polybag, D2= 18 g/polybag and D3= 30 g/polybag. Both of these factors resulted in 9 treatsments combination. Each combination made three replications, so that there are 27 experimental units. Each experimental unit consisted of two plants, so the total crop was 54 plants. The data were statistically analyzed using analysis of variance and the means were tested with Duncan 's New Multiple Range Test (DNMRT) at level of 5%. The research results show that combination of compost bunches empty palm oil and dolomite had show the real effect on the increase in diameter hump of seedlings , but the effect not real on the parameters height of seedlings,increase number of leaves, volume roots, ratio crown rootsand and dry weight of seedlings. Combination compost bunches empty palm oil 112,5 g/polybag and dolomite 18 g/polybag showed better results for the growth of palm oil seedlings. Key words :Â  Palm oil, compost bunches empty, dolomite, sub soil Inceptisol.